La regulación emocional en niños de Inicial II - Alvarado Caicedo, Tais Aymara (2023)
The noble act of belonging to a society in constant transition forces us to face a continuous series of educational demands that revolve around the integrity and wellbeing of children. In this context, emotional education emerges as an essential component for human development and social interactions. This study focuses on the central question of how emotions play a fundamental role in interpersonal and intrapersonal relationships. Theoretical contributions of prominent authors who strengthen the concept of emotional competence and their position in the face of new conceptualizations are shown. In addition it highlights its transcendental importance in the childhood stage. Otherwise, the María Montessori Private Educational Unit in the city of Guayaquil was selected to carry out the observation. During this process, it was found that in most classrooms there is emotional illiteracy on the part of the children. In addition, the level of understanding of emotional regulation by the different educational actors, including managers, teachers and legal representatives, was identified……..